Analysis of Training Management in Improving the Quality of AF Basketball Schools in Kediri - Paquita Putri Utama; Zainal Arifin; Efa Wahyu Prastyaningtyas (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Management of training plays as a determinant of development and stages of achievement that add to the success of quality. AF Basketball School was established to maximize talent's interest in the development of basketball. This research was motivated by the results of the analysis of the researchers to be able to know the management of training on the quality of AF Basketball School Kediri City. Quality in training management efficiently included managing income that can benefit the school, and effectiveness which included increasing achievement from the training carried out. This research used qualitative research. Supported by research triangulation this included interviews and documentation so that it can be analyzed with valid results and can be a benchmark for improving the quality of profits and achievements of the AF Basketball School of Basketball. The results of this study indicate that the analysis of training management in the AF Basketball School can affect the quality of achievement effectiveness and profit efficiency. It was revealed by factor analysis of training from planning, organizing, moving, supervising, which was carried out by the AF Basketball School.